The influence of leadership style and work motivation on employee performance CV. Hody Ceria Bogor - Viona Rachma Putri Suandi (CV. ITTC INDONESIA, 2023)
The results of this study influence leadership style and work motivation on employee performance. The number of employees in this study were 40 employee respondents at CV.Hody Ceria. The method used was a questionnaire research instrument which was distributed to employees of CV.Hody Ceria which was processed using a computer application. This research was conducted. The variables of leadership style and work motivation on performance were obtained by the results of the T and F tests. Results with a value of = 32.933 > Ftable of 3.25 then Ho was rejected (Ha was accepted) and leadership style score T table 32.933 < T table 2.026 Ho1 is rejected (Ha1 is accepted) with a work motivation score Ttable 5.124 > from Ttable 2.026 then Ho2 is rejected (Ha2 accepted). It can be concluded that in the T test if the leadership style has a positive impact on performance and is aligned with work motivation it has a positive impact on performance. From this study, R count = 0.640 with a percentage of 64%. There is a strong relationship between the Variable Leadership Style (X1) and Work Motivation (X2) on Performance (Y). It is proven that there is an influence of Leadership Style (X1) and Work Motivation (X2) on Performance (Y). The remaining variable is 36% by other factors not examined in this study